Workshop Pembuatan Video Pembelajaran Berbasis Animasi untuk Mendukung Program Digitalisasi Sekolah - Meria Ultra Gusteti; Sri Novia Martin; Syariffan Syariffan; Siti Nurhikmah; Pahira Seprilia Antika; Silvi Oktavia (Jurnal Pengabdian Masyarakat PGSD, 2021)
The Covid-19 era that hit the world had an impact on all aspects of life, one of which had an impact on the world of education. Where the learning process at schools is carried out online, one of which is at SMK N 6 Padang. Since the teaching and learning process is carried out online, teachers usually give assignments such as providing material and practice questions to students via WhatsApp. However, in a process like this, learning becomes monotonous and sometimes makes students lazy to learn. The ability of teachers to create IT-based learning media is also still limited. Meanwhile, in the digital era, a teacher is required to be able to adapt and take advantage of existing technology to improve the quality of learning. Therefore, training is given to teachers in schools to create animation-based learning videos using the Animaker application. The method used in this training is a demonstration and direct practice for teachers with assistance in making learning videos. This training is intended so that teachers at SMK N 6 Padang can make interesting learning videos so that students become more enthusiastic in participating in the learning process even though they are online. Besides, this activity is also a support for the school digitization program. The result of this training is that teachers can create animation-based learning videos using the Animaker application